Comparison of RDW-SD and RDW -CV in Chronic Kidney Disease Patients Before and After Hemodialysis - Dzaki Ahmad Fahrezi Amus; Haerani Harun; Jeremy Tanan; Rahma; Nur Syamsi; Christin Rony Nayoan (Fakultas Kedokteran Universitas Malikussaleh, 2026)
Red Cell Distribution Width (RDW) is a prognostic biomarker in chronic kidney disease (CKD), reported as RDW-SD (absolute) and RDW-CV (relative). This study directly compares changes in RDW-SD versus RDW-CV before and after a single hemodialysis (HD) session. This pre-post observational study involved 30 adult CKD patients undergoing routine HD. Blood samples were taken pre-HD and one hour post-HD. RDW-SD, RDW-CV, and other hematological parameters were analyzed using a hematology analyzer (Wilcoxon test). Median RDW-SD was 44.40 fL pre-HD vs. 43.80 fL post-HD (p=0.186); median RDW-CV was 14.35% pre-HD vs. 14.30% post-HD (p=0.052). Neither showed significant acute changes, although hemoglobin and leukocytes increased while platelets decreased. A single HD session does not significantly alter RDW-SD or RDW-CV, confirming both parameters reflect chronic disease status rather than acute procedural effects. Clinical implications: These preliminary findings suggest that RDW-SD and RDW-CV may be considered potential long-term prognostic markers, although this requires confirmation in larger studies.